2020
DOI: 10.1101/2020.06.21.20136523
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Breath-borne VOC Biomarkers for COVID-19

Abstract: Rapid diagnosis of COVID-19 is key to controlling the pandemic. Here we report the potential breath-borne volatile organic compound (VOC) biomarkers for COVID-19. Higher levels of ethyl butanoate were detected in exhaled breath of COVID-19 patients (N=10) than healthy controls/health care workers (N=21), lung cancer (LC) patients (N=7) and backgrounds. In contrast, breath-borne butyraldehyde and isopropanol (an efficient SARS-CoV-2 inactivation agent) were significantly higher for non-COVID-19 respiratory infe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 19 publications
2
48
0
Order By: Relevance
“…acetone), alcohols (e.g. isopropanol, methanol) and an alkadiene (2,4-octadiene) to differentiate between those with and without COVID-19 (4, 31, 32). Furthermore, in a small study using a multi-capillary column coupled ion mobility spectrometry (MCC-IMS), Steppert et al .…”
Section: Discussionmentioning
confidence: 99%
“…acetone), alcohols (e.g. isopropanol, methanol) and an alkadiene (2,4-octadiene) to differentiate between those with and without COVID-19 (4, 31, 32). Furthermore, in a small study using a multi-capillary column coupled ion mobility spectrometry (MCC-IMS), Steppert et al .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the other clinical GC-IMS study conducted by researchers in Beijing, China, suggested several other potential breath-borne VOC biomarkers for COVID-19 (i.e., acetone (C 3 H 6 O), ethyl butanoate, butyraldehyde, and isopropanol). 62 They found that the decrease and rise of acetone (C 3 H 6 O) and ethyl butanoate levels, respectively, due to the changes of metabolites resulting from SARS-CoV-2 infections, were distinctive for COVID-19 patients. 62,63 Moreover, the average measured isopropanol and butyraldehyde for the COVID-19 patients were lower than those for the healthy control, lung cancer, and non-COVID-19 respiratory infection patients.…”
Section: Sensor Characteristics To Exhaled Breathsmentioning
confidence: 99%
“…89 However, in patients with positive COVID-19, acetone was reported to be in a lower proportion, compared to health care worker or healthy control group. 62 Meanwhile, other VOC (i.e., ethyl butanoate) has also been reported as one of signature VOCs in COVID-19 patients where its concentration is slightly higher compared to healthy control. 62 Our breath analysis study will be extended in combination with GC-MS to identify the speci c VOC biomarkers that are distinctive for COVID-19 cases in Indonesia.…”
Section: Genose C19 Performance In Covid-19 Pro Ling Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent reports showed that the potential volatile organic compounds (VOC) marker contain higher ethyl butyrate levels than healthy control ( 76 , 77 ). The markers used by breath analyzers are reported to be related to COVID-19 disruption of respiratory biochemistry resulting from ketosis, inflammatory processes, and gastrointestinal effects ( 78 ).…”
Section: Recently Developed Exclusive Interfaces-based Biosensors For Sars-cov-2 Testing and Covid-19 Diagnosismentioning
confidence: 99%